Analysis of Mitochondrial Bioenergetics of Bloodstream Form of Trypanosoma Brucei - Ielanskyi, Mykyta (Jihočeská univerzita, 2018)
Trypanosoma brucei is a pleomorphic extracellular parasite that represents significant scientific interest due to its early divergence from the eukaryotic lineage and its range of unique adaptations. Among these adaptions are some metabolic pathways that are unconventional and are not fully understood. Among such pathways are the catabolic pathways of the parasite's bloodstream form, in particular those responsible for ATP supply to the parasites' reduced mitochondrion. This thesis investigates the nature of these pathways as well as interactions between them.
Analysis of Mitochondrial Bioenergetics of Bloodstream Form of Trypanosoma Brucei
Keywords: Trypanosome; Mitochondria; ATP ADP Carrier; Succinyl Coenzyme A Synthase; Substrate Phosphorylation; Trypanosome; Mitochondria; ATP ADP Carrier; Succinyl Coenzyme A Synthase; Substrate Phosphorylation